The Place of Abdukayum Yuldoshev's Stories in Modern Uzbek Prose (Eurasian Scientific Herald, 2022)
This article analyzes the development of modern Uzbek prose and explains the features of this genre based on the stories of the famous writer Abdukayum Yuldashev. The guiding principles of prose are also studied through the use of short stories.